THE PECULIARITIES OF SELF-REGULATION OF FUTURE MUSIC TEACHERS DURING THE PRACTICE - Kirliauskienė, Rasa (Proceedings of the International Conference on Education, 2018)
Each teacher compulsorily appears before class. He or she perceives all the emotional experiences characteristic of being in front of the audience. Not only the homeostasis disorder, which appears through physiological symptoms, bothers the students, they are also distracted by the variety of thoughts, which prevents them from focusing and disposing themselves to the performance. Thus, self-regulation is very important in future music teachers’ training. The research has disclosed the factors promoting positive students’ state during lesson, those are: preparation for the lesson, stage experience and experience in conducting lessons, musical skills and personal qualities, positive attitude and confidence. According to respondents, serious preparation improves one’s state in a lesson, while learners feel more interested. The conducting of a lesson is associated with being on stage. Informants have mentioned that musical skills are very important when conducting a music lesson, since perfect singing, use of instruments etc., strengthens teacher’s authority. In addition, positive attitude and confidence are necessary when willing to achieve harmony in class. Furthermore, personal qualities are an important subcategory according to students, when naming the reasons of appearance of stage fright. The evaluation and support are very important for especially sensitive people.